2019
DOI: 10.18203/2320-1770.ijrcog20190299
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vulvovaginal candidiasis in females in the reproductive age group

Abstract: Background: Vulvovaginal candidiasis (VVC) is a common infection among reproductive age group females. The objective of present study is to determine the prevalence of vulvovaginal candidiasis, its distribution and association of risk factors among reproductive age group females, attending the outpatient department of obstetrics and gynaecology of our Prime Medical Centre, Sharjah attached with Prime Hospital, Dubai, United Arab Emirates (UAE).Methods: It was cross-sectional descriptive study over a period of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 10 publications
2
9
1
Order By: Relevance
“…In our study revealed that from 61 patients with diabetes, the incidence of candida spp was 49(80.3%), and this is higher than a study done by (11) and (25) which was (56.5%) and (53.06%) respectively. It has been observed that elevated glucose levels in genital tissues boost yeast adhesion and growth and that vaginal epithelial cells attach to Candida spp.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…In our study revealed that from 61 patients with diabetes, the incidence of candida spp was 49(80.3%), and this is higher than a study done by (11) and (25) which was (56.5%) and (53.06%) respectively. It has been observed that elevated glucose levels in genital tissues boost yeast adhesion and growth and that vaginal epithelial cells attach to Candida spp.…”
Section: Discussioncontrasting
confidence: 60%
“…Vulvovaginitis is a general problem attacking large numbers of females around the globe, vulvovaginal candidiasis (VVC) can becharacterized as signs and symptoms of inflammation of the vulva and vagina with the existence of Candida spp (10) . Incidence of vulvovaginal candidiasis is hard to decide because the clinical diagnosis is usually dependingon symptoms and was not determined by microscopic examination or culture (11) . In the present study, out of 300 symptomatic patients, candidiasis was detected in (57%) (171/300) cases on the culture of the high vaginal swab, and this data is similar to reports by (Rad, etal) (12) which were (66%) and (Kalia, etal) (13) (47%), and lower than that reported by (Ugwa) (14) who reported (84.5%) in North-West Nigeria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Around 54% of total candidiasis were Diabetic which is highly significant in my study. Study conducted by Puranjoy Saha et al 11 was found that only 15.79% of total candidiasis cases were diabetic.Meena Salvi 12 was found that diabetes mellitus was a risk factor for Candida species in 56% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…It was found maximum number Candida species positive cases were multiparous women i.e 18 cases (46%) and then primiparous i.e 12 cases (31%). A study conducted by Meena Salvi 12 showed that prevalence of vulvovaginal candidiasis was found to be high in women who had a parity of more than 2 (40%) and lower in nulliparous (25.4%). And in case of Trichomonas vaginalis positive cases maximum number were multiparous women 3 cases (50%).…”
Section: Discussionmentioning
confidence: 99%